Treatment of Community‐Acquired Pneumonia in Adults: Analysis of the National Dispensing Database. Issue 5 (29th June 2015) - Matuz, Maria; Bognar, Julia; Hajdu, Edit; Doro, Peter; Bor, Andrea; Viola, Reka; Soos, Gyongyver; Benko, Ria
Abstract Crude national ambulatory antibiotic dispensing data (2007–2011) of adult patients (aged between 20 and below 65 years) with CAP were obtained and expressed as DDD per 1000 inhabitants and per day (DID). European quality indicators of antibiotic prescribing were calculated and adherence rate to the national CAP guideline was assessed. Antibiotic use for CAP in adults ranged between 0.27 and 0.30 DID in various years. The most frequently used antibacterials were levofloxacin, co‐amoxiclav and clarithromycin. Antibiotic use in CAP was compliant with the European recommendations in 6.4% in 2007, which decreased to 4.9% by 2011, in contrast to the optimal compliant range of 80–100%. The consumption of fluoroquinolones mounted up to 40% in both genders, which exceeded the recommended range (0–5%) substantially. National guideline also favoured the use of macrolides in the empiric therapy of CAP in otherwise healthy adults; hence, guideline‐concordant antibiotic use ranged between 24.0–32.3%. Agents that were contra‐indicated in the empiric therapy of CAP were also used in 6.5–9.0% in various years. These data reflect some worrisome figures and trends in the outpatient antibiotic treatment of adults with CAP. Clarified and updated national guidelines focusing on outpatients and incentives/regulations to increase guideline concordance are warranted.